The Effect of Service Quality and Trust on Customer Loyalty and Satisfaction: A Case Study of Online Taxi Customers in Indonesia - Harjadi, Dikdik (The journal of contemporary issues in business and government, 2021)
Online taxis have begun to displace conventional public transportation. Dissatisfied with public transportation, users have switched to using online taxis, apparently due to poor service quality and low user trust in modes of public transportation. This research investigated the effect of service quality and trust on customer loyalty and satisfaction, a case study of online taxi customers in Cirebon, Indonesia. This research was conducted using quantitative survey methods. The sample size was 200 customers, and researchers employed judgment sampling and path analysis techniques. The statistical calculations suggested that service quality and customer trust had a positive and significant effect on customer satisfaction. Similarly, service quality had a positive and significant influence – and directly influenced – on customer loyalty. This study concluded that, partially, service quality and trust had a positive impact on customer satisfaction, and that customer loyalty was partly influenced by service quality, trust, and customer satisfaction. The main contribution of this study is the effect of service quality and trust on customer loyalty and satisfaction: a case study of online taxi customers in Cirebon, Indonesia.